Aluminum complex initiated copolymerization of lactones and DL‐lactide to form crystalline gradient block copolymers containing stereoblock lactyl chains. Issue 16 (13th April 2016) - Matsubara, Kouki; Eda, Kiyoka; Ikutake, Yuki; Dan, Misato; Tanizaki, Nao; Koga, Yuji; Yasuniwa, Munehisa
ABSTRACT: The homopolymerization reactions of several lactones, as well as the copolymerization reactions of DL‐lactide with these lactones were investigated using tridentate Schiff base aluminum complexes as the initiators. ε‐Caprolactone and δ‐valerolactone polymerized efficiently at room temperature to afford polyesters, whereas β‐butyrolactone only gave the corresponding oligomer. The copolymerization reactions of DL‐lactide with caprolactone and valerolactone yielded gradient block copolymers where the lactyl blocks formed crystalline stereoblocks as a consequence of the stereoselective polymerization of DL‐lactide in the presence of the aluminum complexes. These polymerization processes were highly controlled in nature, and block copolymerization where caprolactone copolymerized using poly(DL‐lactide)‐Al complex proceeded. The obtained gradient copolymer containing stereoblock lactyl blocks and caproyl blocks were analyzed using WAXD analysis to uncover existence of the crystalline stereoblock lactyl blocks in the copolymer. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2536–2544 Abstract : Homopolymerization of ε‐caprolactone and δ‐valerolactone and copolymerization of DL‐lactide with these lactones were conducted using tridentate Schiff‐base complexes of aluminum as the initiators. The copolymerization yielded gradient block copolymers where the lactyl blocks had the crystalline stereoblock nature derived by stereoselective polymerization of DL‐lactide. The copolymerization profile was also investigated.